Brain Surface Area Alterations Correlate With Gait Impairments in Parkinson’s Disease - Wei, Xuan; Wang, Zheng; Zhang, Mingkai; Li, Min; Chen, Yu-Chen; Lv, Han; Tuo, Houzhen; Yang, Zhenghan; Wang, Zhenchang; Ba, Fang (Frontiers in Aging Neuroscience, 2022)
Parkinson's disease (PD) is a common neurodegenerative disease with progressive gait, cognition, and overall functional decline. Surface area changes are frequently seen with aging. In neurodegenerative diseases, the changes can be evident with disease progression. The current study aimed to study the regional microstructural alterations using surface-based morphometry to correlate with gait measures of the pace and rhythm domains in PD patients. We hypothesize that specific regional surface changes can be associated with PD gait impairments. Surface analysis might provide a useful tool for assessing PD for functional status and specific motor domains, such as gait in PD, and potentially could serve as an imaging marker in adjacent with other imaging markers. Twenty-seven PD patients and 37 healthy controls were included. The clinical assessment included Mini-Mental State Exanimation, PD motor assessment, clinical gait testing and objective/quantitative gait assessment. For patients with PD, all motor and gait testing were performed during both OFF and ON medication states. Three tesla MRI and high-resolution 3D structural images were acquired with a MP-RAGE pulse sequence. Structural image data preprocessing was performed using the DPABISurf toolbox. Clinical characteristics between PD and control group were compared, and correlation between the surface area and behavioral data were analyzed. At left lateral temporal cortex (LTC) and right inferior parietal cortex (IPC), PD patients have significant larger surface areas when compared to controls (P<0.05) using the surface-based morphometry. The surface area changes of the left LTC and right IPC were associated with worse performance of gait assessed by Berg Balance scale and Timed Up and Go during OFF (P<0.01). The left LTC area changes significantly correlated with number of steps, velocity, stride length of the pace domain in the ON state. Our findings suggest that PD is associated with a characteristic regional pattern of larger surface area in left LTC and right IPC. These regional changes were associated with the pace domain of the gait in ON state. Overall, surface-based analyses might provide a useful tool for assessing PD for functional status and specific motor domains, such as gait in PD, and potentially could serve as an imaging marker.